2011
DOI: 10.1007/s00259-011-1925-7
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for integrated imaging modalities in cardiovascular cell-based therapeutics: a clinical perspective

Abstract: Despite preclinical promise, the progress of cell-based therapy to clinical cardiovascular practice has been slowed by several challenges and uncertainties that have been highlighted by the conflicting results of human trials. Most telling has been the revelation that current strategies fall short of achieving sufficient retention and engraftment of cells to meet the ambitious objective of myocardial regeneration. This has sparked novel research into the refinement of cell biology and delivery to overcome thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 153 publications
(187 reference statements)
1
8
0
1
Order By: Relevance
“…For that purpose, BLI has been shown to strongly correlate with the number of cells both in vitro [7] and in vivo [23]. Thus, optical bioluminescence imaging has been adopted in many preclinical studies to longitudinally monitor cell fate, especially in animal models of CHD [13, 24, 20, 23, 25]. Our study confirmed prior observations [5] with poor stem cell survival 24–48 h following delivery into the infarcted heart.…”
Section: Discussionsupporting
confidence: 86%
“…For that purpose, BLI has been shown to strongly correlate with the number of cells both in vitro [7] and in vivo [23]. Thus, optical bioluminescence imaging has been adopted in many preclinical studies to longitudinally monitor cell fate, especially in animal models of CHD [13, 24, 20, 23, 25]. Our study confirmed prior observations [5] with poor stem cell survival 24–48 h following delivery into the infarcted heart.…”
Section: Discussionsupporting
confidence: 86%
“…К сожале нию, несмотря на некоторые различия в эф фективности этих методов доставки клеток, в настоящее время сохранение МСК и их при живление в миокарде остается недостаточно совершенным во всех случаях [143].…”
Section: микрорнк и кардиомиогенная дифферен цировка мскunclassified
“…While direct labelling is used to monitor cell fate only shortly after transplantation, mainly due to the progressive dilution of the signal - as a consequence of cell division - and cell toxicity issues - which may vary depending on the agent and doses used, reporter gene imaging allows long-term assessment of cell fate with longitudinal and repetitive imaging[26,27]. Using this strategy, cells are engineered to over-express or produce de novo an enzyme, receptor or protein: when this protein interacts with an exogenously administered substrate, it results in a signal that can be used to distinguish not only implanted cells from endogenous cells with high specificity, but also modulations in intracellular functions[28].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of spatial resolution and tissue depth penetration, the use of BLI is restricted to small animal studies (rats and mice)[26]. However, this strategy can be adapted to clinically used imaging modalities, such as Positron Emission Tomography (PET) or Single-Photon Emission Computed Tomography (SPECT), using - for instance - thymidine kinase (TK) or human sodium-iodide symporter (hNIS) as reporter genes, respectively[19,27]. Therefore, BLI may be considered as a starting step in the development of novel imaging strategies in high-throughput preclinical studies.…”
Section: Introductionmentioning
confidence: 99%